Employability in people with epilepsy: A systematic review - Wo, M.C.M.; Lim, K.S.; Choo, W.Y.; Tan, C.T. (Elsevier, 2015)
Objectives: People with epilepsy were (PWE) reported to have poorer employment rate. However, the methodologies used differ greatly from one study to another, making global comparison difficult. We aimed to determine the employment rate of PWE globally using a unified definition of employment rate and to summarize the reported positive and negative factors affecting employability in PWE, using a systematic review. Methods: All studies reporting employment rate of PWE were independently assessed. Employment rate was recalculated according to the standard definition by the Bureau of Labor statistics (BLS) of United States and the International Labour Organization i.e. employment rate is the percentage of employed person over the labor force. Results: Of 95 papers reported on employment status of PWE, adjusted employment rate (aER) was shown to be as low as 14% to as high as 89% with a mean adjusted employment rate of 58%. No significant differences in mean of aER was found between continents, or among Asian countries. Employment rate of people with uncontrolled seizures were reported in 16 papers, with a mean adjusted employed rate of 58%. Psychological factors were less frequently reported as compared to clinical and socio-demographical factors, seen in a total of 25 (26%) out of 97 studies. The positive factors leading to successful career in PWE were understudied and needed to be further explored. Conclusion: Employability is multifactorial, including clinical, psychological and social factors. The adjusted employment rate of people with uncontrolled seizures is comparable to those with controlled seizures, supporting the need to explore non-clinical factors.